A comparison of partially premixed methane/air combustion in confined vane-swirl and jet-swirl combustors. Issue 2 (25th January 2023) - Zhao, Xiaoyao; Peng, Weikang; Yu, Xiao; Shi, Baolu
ABSTRACT: The characteristics of partially premixed methane/air combustion in aconfined geometry are experimentally investigated in two types of swirling flows introduced by using avane swirl (VS) and tangential jet swirl (TJS), respectively. To make acomparison, acoaxial jet (CJ) burner is also employed. The fuel and air are individually injected through their own inlets, partially premixed in amixing chamber, and then burned in aconfined cylindrical combustor. In VS and CJ combustors, the fuel is axially injected from the center; while in the TJS combustor the fuel is injected through either acentral inlet or tangential inlet. The geometry swirl number varies from 0 to 3.38. The flame structures, extinction limits, temperature distribution, NOx, CO concentrations and flow velocities are systematically examined to compare the flame characteristics. The detailed observations show that the swirl plays asignificant role in the fuel mixing, flame stabilization, and flame structures. As fuel is axially injected, ayellow flame is established at low airflow rate regardless of the swirl number values. As the airflow rate increases, ablue flame is obtained; the flame extinguishes at avery low global equivalence ratio of 0.25 in the VS and TJS combustors. When fuel and air are tangentially injected, ablue flame similar to premixed one is established; asteady flame is obtained from lean to rich limits (equivalence ratio of 0.5 to 1.68). The temperature is distributed more uniformly in the high swirl TJS combustor, particularly for the one adopts pure tangential jets of fuel and air, in which the measured NOx and CO concentrations are the lowest. The differences were mainly attributed to different mixing modes.